Descobrir-se mulher negra no teatro em Macapá: percurso e desvendamento - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
This work has as main objective research the black women’s writing about the protagonism of firsts black actresses who act in Brazilian scene theatrical and her mains references. Conversation to black women bringing the importance of locate the black women presents in the state of Amapá through the interviews. Also remembering of black women’s discussions in viewpoint social political and to base the theoretical references and contribute with the basic concept this research l appropriated myself of this Knowledge: Aguiar (2018), Berth (2018), Canto (1987, 1998, and 2017)), Carneiro (2003) and so many others. However, the research realized proved that the course of graduation Theatre of the Federal University of Amapá has a fundamental importance in the promotion and dissemination of state culture
Keywords: Memória; Identidade; Mulher negra - Teatro; CNPQ::LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO